MiR‐497 induces apoptosis by the IRAK2/NF‐κB axis in the canine mammary tumour. (15th September 2020) - Zhang, Tao; Feng, Xiujuan; Zhou, Tianhong; Zhou, Ning; Shi, Xue; Zhu, Xinying; Qiu, Jinxia; Deng, Ganzhen; Qiu, Changwei
Abstract: Since companion dogs have the same living environment as humans, they are a good animal model for the study of human diseases; this is especially true of canine spontaneous mammary tumours models. A better understanding of the natural history and molecular mechanisms of canine mammary tumour is of great significance in comparative medicine. Here, we collected canine mammary tumour cases and then assayed the clinical cases by pathological examination and classification by HE staining and IHC. miRNA‐497 family members (miR‐497, miR‐16, miR‐195 and miR‐15) were positively correlated with the breast cancer marker genes p63 and PTEN. Modulation of the expression of miR‐497 in the canine mammary tumour cell lines CMT1211 and CMT 7364 induced apoptosis and inhibited cell proliferation. Mechanistically, IRAK2 was shown to be a functional target of miR‐497 that affects the characteristics of cancer cells by inhibiting the activity of the NF‐κB pathway. Overall, our work reveals the miR‐497/IRAK2/NF‐κB axis as a vital mechanism of canine mammary tumour progression and suggests this axis as a target in breast cancer.